Methyl methacrylate plus carbon dioxide phase equilibria at high pressures - Uzun, NI; Akgün, M; Baran, N; Deniz, S; Dinçer, S (AMER CHEMICAL SOC, 2005)
High-pressure vapor-liquid equilibria data for the binary system methyl methacrylate + carbon dioxide were measured using the static method. Experiments were carried out in the pressure range of (6 to 13) MPa and for temperatures of 323.15, 333.15, 343.15, and 353.15 K. Experimental results were correlated with the Peng-Robinson equation of state using conventional mixing rules with one interaction parameter.
Keywords: DISPERSION POLYMERIZATION; SUPERCRITICAL CO2; BEHAVIOR; STYRENE; LIQUID; Thermodynamics; Chemistry; Engineering